(untitled) (Modern education and development, 2025)
Translation is not merely a linguistic process but also a cultural transfer. Cultural aspects play a crucial role in shaping the meaning and effectiveness of a translated text. Differences in cultural norms, values, traditions, and social contexts often create challenges for translators, who must find ways to convey not only words but also the cultural nuances embedded in the source text. This paper explores the importance of culture in translation, the common cultural challenges faced by translators, and strategies to handle cultural differences to achieve accurate and meaningful translations.